A Paradigmatic Shift For Final Undergraduate Medical Students’ Examination: The Covid-19 Pandemic Approach - Ruhi Fadzlyana Jailani; Siti Asmat Md Arepen; Nadeeya'ayn Umaisara Mohamad Nor; Noor Fadzilah Zulkifli; Suhaila Sanip (UPM, 2024)
Indexed by WOS/SCOPUS/ERA